Evaluasi Program Pemberdayaan Usaha Mina Pedesaan pada Masyarakat Pesisir - Indiradewi, Ni Made Ayu; Marhaeni, A.A. Istri Ngurah (Jurnal Ekonomi Kuantitatif Terapan; 2016: Vol. 9, No. 1, Februari 2016 (pp. 1 - 88)DO - 10.24843/JEKT.2016.v09.i01.p08)
In general, the activity of both fishermen and marine fish farming synonymous with poverty. In order to improve the living standards of fishermen through increased well-being, conducted empowerment as Mina Rural Business Development Program (PUMP). This study aimed to: 1) the effectiveness of the Program PUMP, 2) the level of welfare of fishermen after PUMP program implemented, 3) the constraints in implementing PUMP program, and 4) weaknesses in Program PUMP. This research was conducted in Badung, which includes 11 Business Group (KUBE) in the district of Kuta. Samples in this study amounted to 80 respondents. The method in this research is observation, structured interviews, and in-depth interviews. This research uses descriptive statistical test and Wilcoxon test. Based on the analysis we concluded that the level of success seen PUMP program of input variables, process variables, and output variables in the district of Kuta Badung relatively effective. Public welfare increases after PUMP program implemented.
Keywords: evaluation, empowerment, effectiveness, welfare